Sketch-Based Image Retrieval: Benchmark and Bag-of-Features Descriptors - Eitz, M.; Hildebrand, K.; Boubekeur, T.; Alexa, M. (IEEE transactions on visualization and computer graphics, 2011)
We introduce a benchmark for evaluating the performance of large-scale sketch-based image retrieval systems. The necessary data are acquired in a controlled user study where subjects rate how well given sketch/image pairs match. We suggest how to use the data for evaluating the performance of sketch-based image retrieval systems. The benchmark data as well as the large image database are made publicly available for further studies of this type. Furthermore, we develop new descriptors based on the bag-of-features approach and use the benchmark to demonstrate that they significantly outperform other descriptors in the literature.